Comparative Study of Ibn-e Sina and Mulla Sadra on Perceptions - javad parsaee; Hossein Ghafari (حکمت صدرایی, 2019)
Ontological discussions of knowledge and perception are one of the important issues that philosophers and scientists have commented on. Among the Muslim Philosophers, Ibn-e Sina and Mulla Sadra have discussed the issue of knowledge and perception in detail. According to these two philosophers, knowledge by acquisition is divided into sensual, imaginative, hallucinatory and intellectual. From the viewpoint of Ibn Sina and Mulla Sadra, intellectual knowledge is abstract, but they differ about the nature of perceptions (sensual, imaginative, hallucinatory), that is, whether they are abstract or material in nature. Ibn-e Sina believes that perceptions are impressive in the brain and matter, whereas, Mulla Sadra believes in the abstraction of all perceptions irrespectively. This article, first, provides an explanation about the definition of science and the levels of knowledge; then, it critically looks at Ibn-e Sina's argument about the materiality of perceptions. The article points out that the arguments of Ibn-e Sina is controversial and his view of the materiality of the perceptions is not acceptable. The article then investigates the arguments of Mulla Sadra about the abstract nature of perceptions.